Intervensi Pencegahan Jatuh Pada Lansia Berbasis Keperawatan Keluarga: Tinjauan Sistematis - Didi Kurniawan; Junaiti Sahar; Etty Rekawati; Ratu Ayu Dewi Sartika (Universitas Pahlawan Tuanku Tambusai, 2025)
Falls in the elderly are a serious problem because they can cause physical injuries, such as fractures, head trauma, and even death. Preventing falls in the elderly requires a multidimensional approach that is not only focused on the individual, but also involves the family as the main support unit. This review aims to identify family nursing-based fall prevention interventions. This systematic review method follows the PRISMA framework with article searches through Cinahl, ProQuest, Pubmed, ScienceDirect, Google scholar, and the Cochrane database of systematic reviews. The findings of this review revealed that of the 541 articles identified in the initial stage, nine articles met the eligibility criteria and were retained for further in-depth analysis. The results of the analysis provide insights into fall prevention interventions including; health education, mindfulness and psychoeducation, Otago exercise program, family involvement, fall risk assessment, and home modification. These findings have important implications for community health nurses in providing family nursing care, through empowering the family as the main caregiver in managing fall risk at home.